2021
DOI: 10.1038/s41598-021-92159-2
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of myostatin protects skeletal muscle cells from ischemia reperfusion injury

Abstract: Ischemia reperfusion (IR) injury plays a pivotal role in many diseases and leads to collateral damage during surgical interventions. While most studies focus on alleviating its severity in the context of brain, liver, kidney, and cardiac tissue, research as regards to skeletal muscle has not been conducted to the same extent. In the past, myostatin (MSTN), primarily known for supressing muscle growth, has been implicated in inflammatory circuits, and research provided promising results for cardiac IR injury mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The reason for the muscular repair of neoruscogenin might be related to neoruscogenin's ability to reduce the expression of MSTN because studies have shown that the expression of MSTN in muscle injury tissues is higher than that in normal tissues. 53,54 Taken together, these data manifested that neoruscogenin had the function of repairing muscle injury, which might also have a certain effect on the treatment of muscle atrophy.…”
Section: ■ Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The reason for the muscular repair of neoruscogenin might be related to neoruscogenin's ability to reduce the expression of MSTN because studies have shown that the expression of MSTN in muscle injury tissues is higher than that in normal tissues. 53,54 Taken together, these data manifested that neoruscogenin had the function of repairing muscle injury, which might also have a certain effect on the treatment of muscle atrophy.…”
Section: ■ Discussionmentioning
confidence: 78%
“…Moreover, neoruscogenin treatment up-regulated the protein expression of MyOG and MyHC, markers of myoblast differentiation, suggesting that neoruscogenin promoted myoblast differentiation after muscle injury in vivo. The reason for the muscular repair of neoruscogenin might be related to neoruscogenin’s ability to reduce the expression of MSTN because studies have shown that the expression of MSTN in muscle injury tissues is higher than that in normal tissues. , Taken together, these data manifested that neoruscogenin had the function of repairing muscle injury, which might also have a certain effect on the treatment of muscle atrophy.…”
Section: Discussionmentioning
confidence: 94%
“…The IL-6/JAK-STAT pathway is required for myogenic cell proliferation and differentiation and is known to depend on and respond to upstream stimuli. 11,25,36,38 In the presence of a high dose of LPS, although there were significant increases in the expression levels of target factors examined compared with the expression levels in the no-intervention group of cells, the expression levels of IL-6, Pax7, myostatin, HO-1, eNOS, and HSP90 were similar in the control and LIPUS groups. On the other hand, myostatin expression was decreased by LIPUS, while LIPUS did not alter myogenin expression.…”
Section: Discussionmentioning
confidence: 94%
“…Expression levels of proteins were determined densitometrically using Fiji software after subtracting the background signal. Protein levels were corrected with the positive control and expressed as relative values compared with the T/HS vehicle–pretreated group (48).…”
Section: Methodsmentioning
confidence: 99%